2017
DOI: 10.5539/jfr.v6n4p140
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Palm Oil Consumption on Lipid Profile among Rural Ivorian Youth

Abstract: As palm oil has been qualified as atherogen, we have studied the impact of its consumption on changes of lipid and lipoprotein profiles of young Ivorian healthy subjects living in rural areas. It is a descriptive cross-sectional analytical study of about 120 Ivorian subjects aged 18 to 30 years, including 65 regular consumers of palm oil and 55 subjects consuming that oil periodically as control subjects. Serum concentrations of triglycerides, total cholesterol, HDL, LDL cholesterols and lipoprotein (a) were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
3
2
0
Order By: Relevance
“…Triglyceride levels in both treatment groups showed a non-significant increase. This is in agreement with Alexandre et al (2017) who showed that there were no significant differences in the triglyceride levels between the two treatments, with the subjects who were given palm oil had higher triglyceride levels than the controls. Triglycerides store excess energy from the diet.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Triglyceride levels in both treatment groups showed a non-significant increase. This is in agreement with Alexandre et al (2017) who showed that there were no significant differences in the triglyceride levels between the two treatments, with the subjects who were given palm oil had higher triglyceride levels than the controls. Triglycerides store excess energy from the diet.…”
Section: Discussionsupporting
confidence: 92%
“…HDL-C levels in both the treatment groups decreased but without significant differences. These are in line with Alexandre et al (2017) who recruited 120 healthy young volunteers (18 -30 years) with similar eating habits, regardless of the amount of palm oil consumed in Ivory Coast, Abidjan, and West Africa, and showed that there was no significant difference in HDL-C levels between subjects. Decreased HDL-C levels are also associated with the risk of heart disease and development of oxidative stress.…”
Section: Discussionsupporting
confidence: 86%
“…Analysis of the anthropometric parameters of the study population showed that the weight of palm oil consumers did not vary significantly compared to the controls. This result is comparable to that of Aké Aké et al [24] who showed that the consumption of palm oil by the young rural population of Grand for the controls, during a study concerning the effects of palm oil consumption on the nutritional status of a young rural population in Grand-Alépé (Côte d'Ivoire). This study reveals that both study groups were hypotensive with 11.38 / 7.23 and 11.53 / 7.47 as systolic and diastolic blood pressures for controls and consumers, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…(2018) China Randomized, parallel, single-blind 88 M & F aged 20–40 y 16 w POl 20–22 g per day No significant different in LDL-C and HDL-C Ng et al. (2018) Malaysia Randomized, double – blind, parallel 23 M & 67 F, aged 20–60 8 w POl 2 cupcakes and 5 pieces of cookies (33% w/w POl per day) ↓ weight gain, ↓ changes in body fat and leptin concentration Alexandre et al. (2017) Côte d’Ivoire Randomized, cross-sectional 120 M & F aged 18–30 y 6 w PO 25 g ↓ cholesterol, no changes in lipid and lipoprotein profile Hyde et al.…”
Section: Palm Oil and Healthmentioning
confidence: 99%
“…The authors found that when PO used for cooking, it only increased blood pressure and total cholesterol in women compared to peanut oil ( Aung et al., 2018 ). Meanwhile, PO reduced the cholesterol level in healthy youth ( Alexandre et al., 2017 ). Previously, Kabagambe et al.…”
Section: Palm Oil and Healthmentioning
confidence: 99%